Development and Motion Testing of a Robotic Ray. (5th October 2015) - He, Jianhui; Zhang, Yonghua
Abstract : Biomimetics takes nature as a model for inspiration to immensely help abstract new principles and ideas to develop various devices for real applications. In order to improve the stability and maneuvering of biomimetic fish like underwater propulsors, we selected bluespotted ray that propel themselves by taking advantage of their pectoral fins as target. First, a biomimetic robotic undulating fin driven propulsor was built based on the simplified pectoral structure of living bluespotted ray. The mechanical structure and control circuit were then presented. The fin undulating motion patterns, fin ray angle, and fin shape to be investigated are briefly introduced. Later, the kinematic analysis of fin ray and the whole fin is discussed. The influence of various kinematic parameters and morphological parameters on the average propulsion velocity of the propulsor was analyzed. Finally, we conclude that the average propulsion velocity generally increases with the increase of kinematic parameters such as frequency, amplitude, and wavelength, respectively. Moreover, it also has a certain relationship with fin undulating motion patterns, fin ray angle, fin shape, and fin aspect ratio.